Improvement of the Institution of Legal Liability Under Election Law - Ya. A. Konovalchikov (Сибирское юридическое обозрение)
The present article is devoted to the development of the institution of legal responsibility in the election law. To improve the human rights function the author suggests introducing the institution of the Commissioner for the protection of voting rights.